Mengungkap maksud tuturan “Memang Saya Belum Dapat Hidayah” Basuki Tjahaya Purnama: Analisis Wacana Pragmatik. - Rohmat (HUMANISTIKA : Jurnal Keislaman, 2018)
The study want to explain the maening of "I have not got hidayah" which is spoken by Basuki Tjahaja Purnama (BTP). For some Muslems these utterence mean positive, therefore, it give simpatic for non_muslem’s speaker.To explain othe meaning of a certain utterence need a language analisys callad Discourse Analysis or Pragmatic Language Analisys (PLA). PLA is a study about the use of language which try to elaborate language, spoken or verbally with its contex. The basic concept of PLA as explained by Wijana is Spoken’s contex, spoken’s act, Implicatu, Principle of teamwork, and unpolitely. Discourse Analisys is comphrenship analisys to understand the spoken’s utterence which make some mis understanding.The results shows those utterence is just to guide some opinions of the listeners in order to act casually to Islam. It is not get some simpatic.